2022
DOI: 10.1063/5.0087001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of titanium doping and pulsing conditions on the analog temporal response of hafnium oxide based memristor synapses

Abstract: Hafnium oxide non-volatile memories have shown promise as an artificial synapse in neuromorphic computing architectures. However, there is still a need to fundamentally understand how to reliably control the analog resistance change induced by oxygen ions that partially rupture or re-form the conductive filament. In this work, the impact of measurement conditions (pulse amplitude and pulse width) and titanium dopants on the analog resistance change of atomic layer deposited hafnium oxide memristor synapses are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 74 publications
0
14
0
Order By: Relevance
“…Even though our primary goal was to analyze the resistive switching performances of HfO x /AlO y (D1) and AlO y /HfO x (D2) devices, we measured the I – V characteristics of all four devices, especially for the forming (if required), reset, and set operations. As we described in our recently published articles, , we used the optimized test conditions and protocols for all I – V characterizations, including forming and prestabilization of the CFs. We then analyzed the switching performance of all the devices and reported the optimized results.…”
Section: Resultsmentioning
confidence: 99%
“…Even though our primary goal was to analyze the resistive switching performances of HfO x /AlO y (D1) and AlO y /HfO x (D2) devices, we measured the I – V characteristics of all four devices, especially for the forming (if required), reset, and set operations. As we described in our recently published articles, , we used the optimized test conditions and protocols for all I – V characterizations, including forming and prestabilization of the CFs. We then analyzed the switching performance of all the devices and reported the optimized results.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, as reported, the RS process in FTJs, which can reach ˜nA, consumes much less energy in terms of current than the comparison VCM [79]. Additionally, the doping effect has been demonstrated to significantly influence the energy consumption of memristive devices based on various RS mechanisms [80][81][82]. For example, Tan et al [83] demonstrated that the introduction of nickel doping in HfO x can reduce the energy consumption and enhance the multilevel resistance behavior under the same pulse operation.…”
Section: Applications Scenariosmentioning
confidence: 89%
“…Traditional artificial neural networks based on von-Neuman computing consume significant energy and are facing challenges for data-intensive tasks due to the physical separation of memory and logic processing. , Taking inspiration from biological cognition, neuromorphic computing aims to enable artificial intelligence to perform closer to biological cognition for complex tasks such as self-driving, language translation, pattern and speech recognition, and real-time health monitoring. …”
Section: Introductionmentioning
confidence: 99%